How to Get Promoted 101: Hooking Your OB Students Early With a "What's In It for Me?" Opener. (March 2019) - Mullane, Kenneth
Organizational behavior (OB) students often have difficulty understanding how individual-, group-, and organization-level OB concepts interact to influence employee behavior in the workplace. As a result, students may disengage from the class. Yet the simple prompt of asking students "How do you get promoted?" serves as an effective engagement trigger that helps students link course objectives to valued outcomes. The purpose of this article is to describe a highly interactive, in-class exercise and demonstrate how it can increase in-class participation, help students visualize and appreciate what OB represents, and provide students with a conceptual roadmap for the semester. Due to the learning objectives and format of this exercise, it is intended for undergraduate OB students in a traditional, face-to-face classroom.